Quick Response Code (Qr Code) Assistance in Realizing the Digitalization of Public Services at the Religious Affairs Office of the Pelayangan Sub-District of Jambi City - Sayuti; Qibtiyah, Mariatul; Hasan, Hadri; Sibawaihi, Muhammad; Nasbah (Amala Jurnal Pengabdian Kepada Masyarakat, 2023)
This article is the result of Community Service (PkM) at the Office of Religious Affairs (KUA) Pelayangan District, Jambi City. KUA Pelayangan as one of the public service agencies must be able to provide public servants, especially digital public services, which at this time have become a necessity for people in the digital era. One alternative form of service digitization is by applying the Quick Responses Code (QR Code).  The PkM team provided assistance to Pelayangan KUA employees to utilize the QR Code in serving the community. By using the Asset Based Community Development (ABCD) method which has the principle that everything leads to the context of understanding and internalizing assets, potential, strength and utilization independently and maximally. The process of implementing this service activity is carried out by observation, socialization, discussion, mentoring, monitoring and evaluation. The results of this PkM program assistance show that KUA employees, as potential human resources, are able to adapt well to understand and even apply the QR Code in services. Not only the KUA, the community also gave a positive response to the use of QR Code in the current digital era.